The enigmatic marine reptile nanchangosaurus from the lower triassic of Hubei, China and the phylogenetic affinities of Hupehsuchia. - Xiao-hong Chen (Public Library of Science (PLoS), 2014)
The study of the holotype and of a new specimen of Nanchangosaurus suni (Reptilia; Diapsida; Hupehsuchia) revealed a suite of hitherto unrecognized characters. For example, Nanchangosaurus has bipartite neural spines and its vertebral count is nearly identical to that of Hupehsuchus. It differs from the latter in having poorly developed forelimbs despite the advanced ossification in the rest of the skeleton. Other differences all pertain to hupehsuchian plesiomorphies retained in Nanchangosaurus, such as low neural spines. The relationship of Hupehsuchia within Diapsida was analyzed based on a data matrix containing 41 taxa coded for 213 characters, of which 18 were identified as aquatic adaptations from functional inferences. These aquatic adaptations may be vulnerable to the argumentation of character homology because expectation for homoplasy is high. There is an apparent incongruence between phylogenetic signals from aquatic adaptations and the rest of the data, with aquatic adaptations favoring all marine reptiles but Helveticosaurus to form a super-clade. However, this super-clade does not obtain when aquatic adaptations were deleted, whereas individual marine reptile clades are all derived without them. We examined all possible combinations of the 18 aquatic adaptations (n = 262143) and found that four lineages of marine reptiles are recognized almost regardless of which of these features were included in the analysis: Hupehsuchia-Ichthyopterygia clade, Sauropterygia-Saurosphargidae clade, Thalattosauria, and Helveticosaurus. The interrelationships among these four depended on the combination of aquatic adaptations to be included, i.e., assumed to be homologous a priori by bypassing character argumentation. Hupehsuchia always appeared as the sister taxon of Ichthyopterygia.